Limits of the Obligation to Seek Knowledge and Teach It and Stages in Islamic Education (Gender Studies Perspective) - Emha Dzia'ul Haq (Journal of Contemporary Gender and Child Studies, 2023)
This article aims to determine the limits of a person's obligations in seeking knowledge and teaching it as well as the stages in an Islamic perspective. Qualitative research was chosen in this paper to reveal data using data collection techniques from several sources. Based on these results, it was found that there are no limits to the pursuit of knowledge, which has been explained in the hadith of the Prophet, which means "pursue knowledge from the cradle to the grave", and the pursuit of knowledge has no limits or exceptions, whether men or women are the same. And the teaching varies according to age level. Teaching methods for early childhood cannot be equated with teaching teenagers or adults.